Pesticides and polychlorinated biphenyls (PCBs) contamination and ecotoxicity in estuarine biota - Cardoso, João Pedro Pereira Azedo (2022)
Tese de mestrado, Ciências do Mar, 2022, Universidade de Lisboa, Faculdade de Ciências